Kesaksian Non Muslim Sebagai Alat Bukti Dalam Perkara Perceraian Menurut Hukum Islam (Studi Kasus di Pengadilan Agama Curup) - Fuadi, Ahmad (Institut Agama Islam Negeri (IAIN) Curup, 2022)
In the examination of the case in the Religious Court, the persons who file the lawsuit must bring in evidence, one of which is the evidence of witnesses. So important is the role of proof with testimony, almost in every process of examining cases there is always testimony. However, there is a case filed by the plaintiff before the trial in which the witness presented by the plaintiff is a witness who is not Muslim (Non Muslim), while in Islamic law the majority of scholars absolutely do not allow non-Muslim testimony to be heard. The issue raised in this study is